Modelo de comercialización del maní (arachis hypogaea l.) dirigido a los productores del sitio San Pablo – Roma, cantón Tosagua. - Calderón Figueroa, Jonathan Rolando (2011)
This work is primarily to establish a marketing model that allows small peanuts producers to facilitate a better trade of their product in Roma and San Pablo communities in Tosagua. In order to development this research there were used as tools surveys and statistical graphs that allowed to analyze and diagnose the trades reality in this community. It determined that the product delivered to merchants was done individually, thus it enables the traders to unfavorable conditions for the producers. By this reason it developed a specific marketing plan for peanut producers, the same that includes corporate and marketing strategies, The determinants factors for the formation of trade associations, with strategies was evident with financial benefits in the marketing process , which constitutes a fundamental alternative not only in order to improve the social and economical development of the community, but also to improve the technical development of production and marketing process.